2000
DOI: 10.1063/1.373528
|View full text |Cite
|
Sign up to set email alerts
|

X-ray investigations of the molecular mobility within polymer surface gratings

Abstract: The physical origin of surface relief patterning on amorphous polymer films containing azobenzene-side chains induced by holographic exposure with visible light of about 450 nm is not yet fully understood. To understand the nature of the induced material transport is of special interest to describe the dynamic processes occurring in thin films below the glass transition temperature TG. Thus, we investigated films made from the polar (poly {4′-[2-(methacryloxy) ethyl]-ethyl}amino-4-nitroazobenzene, TG=129 °C) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…401 X-ray investigations are also very powerful in analyzing the surface morphology and the molecular mobility. 402,403 Some very interesting developments have appeared in the recent literature. In a series of papers, Japanese researchers from Toyota have demonstrated that the optical near filed induced by depositing a series of polystyrene spheres on an azo polymer film allows the creation of very regular patterns on the film surface.…”
Section: Massive Macroscopic Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…401 X-ray investigations are also very powerful in analyzing the surface morphology and the molecular mobility. 402,403 Some very interesting developments have appeared in the recent literature. In a series of papers, Japanese researchers from Toyota have demonstrated that the optical near filed induced by depositing a series of polystyrene spheres on an azo polymer film allows the creation of very regular patterns on the film surface.…”
Section: Massive Macroscopic Motionsmentioning
confidence: 99%
“…Time dependent analysis has proven useful to investigate the formation of half-period SRG as well . X-ray investigations are also very powerful in analyzing the surface morphology and the molecular mobility. , …”
Section: Massive Macroscopic Motionsmentioning
confidence: 99%
“…, which has a glass transition temperature of T g = 129 °C and a broad maximum of absorption at approximately λ ≈ 500 nm [18] .…”
Section: Methodsmentioning
confidence: 99%
“…Typically, SRG have a period in the range of micrometers and a modulation depth of a few hundreds of nanometers, meaning that the motion takes place at a scale several orders of magnitude higher than that of the photochromic molecule alone (Figure c). The grating spacing Λ g can be modulated by tuning the incident angle θ of the interfering beams at a wavelength λ, following the equation: Even if SRG are widely explored in the literature, the mechanism of their formation is still under debate. , Briefly, two main ideas are usually opposed: (i) the photofluidization concept and (ii) the alignment effect. For the former, it is suggested that the continuous trans → cis and cis → trans isomerization processes soften the polymer matrix around the photochromic molecules like a thermal fluidization.…”
Section: Motion From Photochromic Molecular Switchesmentioning
confidence: 99%